A novel method for the welding of tailor-welded blanks with different thicknesses based on the diode laser source. (September 2021) - Lin, Xingchen; Wang, Pengfei; Zhu, Hongbo; Zhang, Yawei; Ning, Yongqiang; Wang, Lijun
Highlights: A novel welding model is introduced for the butt welding of tailor-welded blanks. Inspection results prove that this method can satisfy the industrial requirement. It can simplify processing procedures and improve production efficiency. Abstract: Due to weld defects occurred in the traditional laser welding of tailor-welded blanks with different thicknesses, a novel processing method is proposed in this paper. In this method, thin and thick metal plates are obliquely cut and then butt jointed to form an eave-like structure. When a laser beam irradiates on the marginal area of the thick plate, the molten metal flows into the gap and welds two plates together. Using this method, stainless steel tailor-welded blanks with a plate thickness combination of 2.0 mm and 1.0 mm are successfully welded by a diode laser source, and welded samples are free from cracks and pores. This method supplies a concise and quick processing way for the processing of tailor-welded blanks in industry.